PENGARUH METODE KOOPERATIF TEKNIK NHT TERHADAP HASIL BELAJAR DAN RESPON SISWA PADA MATERI KONSEP MOL - Sarpianto, Sarpianto; Enawaty, Eny; Sarti, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether there is a difference between the learning outcomes of students who are given cooperative learning techniques Numbered Heads Together (NHT) with students given conventional learning on mole concept materials, the influence of cooperative learning techniques NHT in improving learning outcomes and student responses to learning cooperative NHT technique on mole concept material. The form of research used is quasi experimental design with